Genetic diversity study and phylogenetic analysis of Echinococcus granulosus sensu lato infecting buffaloes in India using NAD1, COX1 and ITS1 genes - S. Anandu; M. K. Vijayasarathi; Malviya Aditi; K. Varsha; H. Palampalle; A. Sangaran; S. Samanta; S. Bandyopadhyay; M. Sankar (Molecular Biology Reports, 2026)

In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Seasonal characterisation of iron-binding ligands in the South Atlantic sector of the Southern Ocean (Scale cruises, 2019) - V. Coussy; J.M. Santana-Casiano; M. González-Dávila; D. González-Santana; T.N. Mtshali; T.J. Ryan-Keogh; S. Samanta; A.N. Roychoudhury; A.G. González (Marine Environmental Research, 2026)

Modulating IL-1β-induced pro-atherogenic endothelial responses through drug repurposing - Kundan Solanki; Sk Rameej Raja; Sunanda Samanta; P. S. Shishira; Anjali Roy; Parimal Kar; Swati Biswas; K. M. Ramkumar; Mirza S. Baig (Inflammopharmacology, 2026)

Distribution and mobility of heavy metals in the sediments of a highly urbanized tropical estuary (Netravathi–Gurupur estuary, southwestern coast, India) - Sonalika Sahoo; Ajoy Saha; D. J. Sarkar; M. Feroz Khan; M. E. Vijaykumar; S. Samanta; B. K. Das; Lokenath Chakraborty; Tania Kayal (Environmental Geochemistry and Health, 2026)

Marine carbon dioxide removal (mCDR) in the Indian seas: current understanding, regional opportunities, and future directions - Sumit S. Sonar; Susmita Raulo; Suchismita Srichandan; Dhanya M. Lal; Sanjiba K. Baliarsingh; Alakes Samanta; Sudheer Joseph; T.M. Balakrishnan Nair (Mitigation and Adaptation Strategies for Global Change, 2026)

Long-term variability of chlorophyll- a in the north-western Bay of Bengal: linking phytoplankton size class and diatom dynamics - Suchismita Srichandan; Amit Kumar Jena; Alakes Samanta; Susmita Raulo; V. V. S. S. Sarma; Sanjiba Kumar Baliarsingh; Amit Maharana; Kamal Kumar Barik (International Journal of Remote Sensing, 2026)

Managing sustainable agricultural supply chains in smart cities with IoT and blockchain - Saikat Samanta; Achyuth Sarkar; Jitendra Singh Yadav; Atul Srivastava; Vijay Shankar Sharma; Jagadish S. Kallimani; Siddhanta Kumar Singh (Environment, Development and Sustainability, 2026)

Satellite retrieval of phytoplankton size class biomass: algorithm evaluation and long-term patterns in the northern Arabian Sea - Sanjiba Kumar Baliarsingh; Alakes Samanta; P. Minu; S. Ayana; Aneesh A. Lotliker (International Journal of Remote Sensing, 2026)

Molecular Epidemiology of Multi-Drug Resistant E. coli Isolated from Poultry Birds in Six Agroclimatic Zones of West Bengal, India: A Cross-Sectional Study - Md Habib; J. Banerjee; S. Batabyal; P. K. Nanda; A. K. Das; U. K. De; I. Samanta; P. Dandapat; S. Bandyopadhyay (Indian Journal of Microbiology, 2025)

Oxygen vacancies driven Pd - MoO3 / f - MWCNTs nanocomposite for electrochemical sensing of Pb (II) - Upasana Choudhari; Pragati Shukla; S. Samanta; N.S. Ramgir; Shweta Jagtap (Environmental Research, 2025)

From ocean to opportunity: Upcycling fishing net waste into high-performance, reprocessable nylons - S. Vimal Kumar; B.D.S. Deeraj; Siddhesh Sadashiv Rege; A. Moulishwar Reddy; S. Ram Prasanth; Sk Safikul Islam; Indranil Dey; Ketaki Samanta; Ashok Misra; Suryasarathi Bose (Chemical Engineering Journal, 2025)

Toxic impact of aluminium on the natural phytoplankton community during spring in the Atlantic sector of the Southern Ocean - C. Demasy; A. Singh; S. Samanta; T.J. Ryan-Keogh; A.N. Roychoudhury (Journal of Experimental Marine Biology and Ecology, 2025)

Streptomyces sp. M7 immobilized cells as bioinoculant for enhanced atrazine removal in biobed-type biomixtures - Samanta K. González; Juliana M. Saez; Lourdes M. Maldonado; Enzo E. Raimondo; Gabriela E. Briceño; Claudia S. Benimeli (Journal of Environmental Chemical Engineering, 2025)

Impact of environmental, social, and governance disclosures on debt financing decisions: evidence from India - Poornima S; Gopalakrishna B V; Mithun Samanta (Environment, Development and Sustainability, 2025)

Betalain-containing foods and their antitumoral potential: A comprehensive review of in vitro and in vivo evidence - Pedro Martínez-Rodríguez; Marina Malo-García; Samanta Hernández-García; Sepideh Youssefi; Abdolrahman S. Nateri; M. Alejandra Guerrero-Rubio; Fernando Gandía-Herrero (Trends in Food Science & Technology, 2025)

Novel IgM-based lateral flow assay for diagnosis of congenital Chagas disease - Luz M. Peverengo; Leandro E. Peretti; Maria B. Warszatska; Guillermo Moscatelli; Samanta Moroni; Nicolas Gonzalez; Claudio L. A. Berli; Jaime M. Altcheh; Iván S. Marcipar; Nazarena Pujato (Infectious Diseases, 2025)

Validation and assessment of Potential Fishing Zone (PFZ) dynamics along the southwest coast of India through environmental proxies and trophic guild analysis - Dhanya Mohan Lal; Harisha; Alakes Samanta; Sudheer Joseph; S Suresh Kumar; Sanjiba Kumar Baliarsingh; T M Balakrishnan Nair (Environmental Impact Assessment Review, 2025)

Salinity variations drive the phytoplankton dynamics in the Gangetic estuary: insights from the modelling approach for species responses and pollution indicators along the longitudinal estuarine gradient - Sangeetha M. Nair; Pranab Gogoi; Dibakar Bhakta; R.K. Manna; Chayna Jana; Abhijita Sengupta; S.K. Manna; S. Samanta; B.K. Das (Marine Pollution Bulletin, 2025)

The conformational preference of dynamic crosslinker modulates the ‘closed-loop’ circular economy in polypropylene vitrimer - Indranil Dey; Ketaki Samanta; Sayon Ghosh; Tanay Debnath; Samir Mandal; Siddhesh Sadashiv Rege; S. Vimal Kumar; Sk. Safikul Islam; Ashok Misra; Suryasarathi Bose (Chemical Engineering Journal, 2025)

Trace metal accumulations in commercially important fish and crab species from impacted tropical estuary, India: implications on human health risk assessment - Ajoy Saha; B. K. Das; Chayna Jana; D. J. Sarkar; Sonalika Sahoo; S. Samanta; Vikas Kumar; M. E. Vijaykumar; M. Feroz Khan; Tania Kayal (Environmental Geochemistry and Health, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Molecular identification and genetic variability of equine and bovine ocular setariasis in india: molecular profiling by mitochondrial genes - S. Anandu; Guntru Narasimha Tanuj; M. K. Vijayasarathi; K. M. Manjusha; Subhamoy Samanta; Subhashish Bandyopadhyay; M. Sankar (Molecular Biology Reports, 2024)

Tide–surge interaction observed at Singapore and the east coast of Peninsular Malaysia using a semi-empirical model - Zhi Yang Koh; Benjamin S. Grandey; Dhrubajyoti Samanta; Adam D. Switzer; Benjamin P. Horton; Justin Dauwels; Lock Yue Chew (Ocean Science, 2024)
Tide–surge interaction plays a substantial role in determining the characteristics of coastal water levels over shallow regions. We study the tide–surge interaction observed at seven tide gauges along Singapore and the east coast of Peninsular Malaysia, focusing on the timing of extreme non-tidal residuals relative to tidal high water. We propose a modified statistical framework using a no-tide–surge interaction (no-TSI) null distribution that accounts for asymmetry and variation in the duration of tidal cycles. We find that our modified framework can mitigate false-positive signals of tide–surge interaction in this region. We find evidence of tide–surge interaction at all seven locations, with characteristics varying smoothly along the coastline: the highest non-tidal residuals are found to occur most frequently before tidal high water in the south, both before and after tidal high water in the central region, and after tidal high water in the north. We also propose a semi-empirical model to investigate the effects of tidal-phase alteration, which is one mechanism of tide–surge interaction. Results of our semi-empirical model reveal that tidal-phase alteration caused by storm surges is substantial enough to generate significant change in the timing of extreme non-tidal residuals. To mitigate the effect of tidal-phase alteration on return level estimation, skew surge can be used. We conclude that (1) tide–surge interaction influences coastal water levels in this region, (2) our semi-empirical model provides insight into the mechanism of tidal-phase alteration, and (3) our no-TSI distribution should be used for similar studies globally.

Assessing nine devices to reduce bycatch in the pink shrimp Penaeus paulensis fisheries: Lessons from field experiments with fyke nets - Samanta Silveira; Dérien L.V. Duarte; Lucas dos S. Rodrigues; Luiz Felipe C. Dumont (Regional Studies in Marine Science, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Assessing the trophic status of a tropical microtidal estuary applying TRIX and Random Forest – A combined approach - Pranab Gogoi; Sanjoy Kumar Das; Chayna Jana; Basanta Kumar Das; Ajoy Saha; Karankumar Ramteke; A.K. Jaiswar; S. Samanta; C.M. Roshith (Marine Pollution Bulletin, 2024)

Assessment of water quality of Netravathi-Gurupur estuary, India through chemometric approach for fisheries sustainability - Sonalika Sahoo; Ajoy Saha; M.E. Vijaykumar; M. Feroz Khan; S. Samanta; Sibina S. Mol; B.K. Das (Marine Pollution Bulletin, 2024)

An integrated buoy-satellite based coastal water quality nowcasting system: India's pioneering efforts towards addressing UN ocean decade challenges - T.M. Balakrishnan Nair; V.V.S.S. Sarma; Aneesh A. Lotliker; K.R. Muraleedharan; Alakes Samanta; Sanjiba Kumar Baliarsingh; S. Shivaprasad; T.R. Gireeshkumar; Susmita Raulo; S.P. Vighneshwar; R Venkat Shesu; Murali Krishna; et al. (Journal of Environmental Management, 2024)

Trace metals and pesticides in water-sediment and associated pollution load indicators of Netravathi-Gurupur estuary, India: Implications on coastal pollution - Ajoy Saha; B.K. Das; D.J. Sarkar; S. Samanta; M.E. Vijaykumar; M. Feroz Khan; Tania Kayal; Chayna Jana; Vikas Kumar; Pranab Gogoi; Arnab Roy Chowdhury (Marine Pollution Bulletin, 2024)

Supplementing graded levels of Fish oil in the feeds of Labeo rohita fingerlings: Effects on tissue n-3 LC-PUFA deposition, Δ6 fad gene expression, blood metabolites and fish performance - Mamata Mohapatra; Avinash Pradhan; Ashis Saha; S. Ferosekhan; Baidya Nath Paul; Sangram Ketan Sahoo; Mrinal Samanta; Shiba Shankar Giri (Animal Feed Science and Technology, 2023)

Assessing the watershed-scale effects of tillage management on surface runoff and sediment loss using a Curve Number-precipitation relationship based approach - Sayantan Samanta; Srinivasulu Ale; Dianna K. Bagnall; Cristine L. S. Morgan (Journal of Hydrology, 2023)

Statistical and geostatistical modelling approach for spatio-temporal assessment of river water quality: a case study from lower stretch of River Ganga - R. K. Raman; M. Bhor; R. K. Manna; S. Samanta; B. K. Das (Environment, Development and Sustainability, 2023)

Molecular characterization and serodiagnostic evaluation of the Echinococcus ortleppi recombinant glutaredoxin 1 protein for cystic echinococcosis in buffalo (Bubalus bubalis) - K.A. Yashica; S. Samanta; R. Balaji; V. Jawalagatti; M. Silamparasan; S. Anandu; A. Rialch; S.C. Gupta; Anup Kumar Tewari (Veterinary Parasitology, 2023)

Occurrence of canine parvovirus type 2c in diarrhoeic faeces of dogs in Kolkata, India - S. Abhiram; T. Mondal; S. Samanta; K. Batabyal; S. N. Joardar; I. Samanta; D. P. Isore; S. Dey (VirusDisease, 2023)

Antibacterial effect of kitchen herbs against pathogenic multidrug-resistant E. coli isolates from calf diarrhoea - Saroj Rai; M. Kumar; R. Jas; G. P. Mandal; I. Samanta; M. Rajendar; S. Tripura; S. K. Das; M. Mondal; D. K. Mandal (Tropical Animal Health and Production, 2023)

Sea Surface Temperature and Phytoplankton Abundance as Crucial Proxies for Green Noctiluca Bloom Monitoring in the Northeastern Arabian Sea: A Case Study - Nittala S. Sarma; Sanjiba Kumar Baliarsingh; Aneesh Anandrao Lotliker; Sudarsana Rao Pandi; Alakes Samanta; Suchismita Srichandan (Ocean Science Journal, 2023)

Understanding Responses of Atmospheric Pollution and its Variability to Contradicting Nexus of Urbanization–Industrial Emission Control in Haldia, an Industrial City of West Bengal - Naval Kishor Yadav; Shreyashi S. Mitra; Abhisek Santra; Amiya Kumar Samanta (Journal of the Indian Society of Remote Sensing, 2023)

Geochemical distribution and forms of phosphorus in the surface sediment of Netravathi-Gurupur estuary, southwestern coast of India - Ajoy Saha; M.E. Vijaykumar; B.K. Das; S. Samanta; M. Feroz Khan; Tania Kayal; Chayna Jana; Arnab Roy Chowdhury (Marine Pollution Bulletin, 2023)

Assessment of Spatial and Temporal Changes in Water Quality of a Tropical River in Southern Western Ghats, Kerala, India, Using Physicochemical Quality Indices and Multivariate Analysis - Ajoy Saha; T. T. Paul; Deepa Sudheesan; Sravan Kumar Sharma; V. R. Suresh; B. K. Das; S. Manoharan; M. E. Vijaykumar; S. Samanta; Chayna Jana (Natural Resources Research, 2022)

Systomus spilurus (Günther, 1868) Cyprinidae, A New Distribution Record from Narmada Riverine Biodiversity, Gujarat, India - Dibakar Bhakta; B. K. Das; Suhas P. Kamble; Sonia Solanki; Debarghya Maji; A. K. Sahoo; S. Samanta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Understanding the synergistic relation between land surface temperature and different biophysical parameters in Haldia industrial city of India - Naval Kishor Yadav; Abhisek Santra; Amiya K. Samanta; Akhilesh Kumar; Shreyashi S. Mitra; Debashis Mitra (Arabian Journal of Geosciences, 2021)

Effects of intranasal guanosine administration on brain function in a rat model of ischemic stroke - Gabriel C. Müller; Samanta O. Loureiro; Letícia F. Pettenuzzo; Roberto F. Almeida; Evandro Y. Ynumaru; Pedro A. Guazzelli; Fabíola S. Meyer; Mayara V. Pasquetti; Marcelo Ganzella; Maria Elisa Calcagnotto; Diogo O. Souza (Purinergic Signalling, 2021)

Effect of Proline on Cell Death, Cell Cycle, and Oxidative Stress in C6 Glioma Cell Line - Andréa Gisiane Kurek Ferreira; Helena Biasibetti-Brendler; Daniele Susana Volkart Sidegum; Samanta Oliveira Loureiro; Fabrício Figueiró; Angela T. S. Wyse (Neurotoxicity Research, 2021)

Finfish Diversity of River Narmada and Its Tributaries - Dibakar Bhakta; Sonia Solanki; Nirali Vadhel; W. Anand Meetei; Suhas P. Kamble; G. Chandra; S. Samanta; B. K. Das (Proceedings of the Zoological Society, 2020)

Metal contaminations in sediment and associated ecological risk assessment of river Mahanadi, India - S. Samanta; Vikas Kumar; S. K. Nag; R. K. Raman; K. Saha; S. Bandyopadhyay; B. P. Mohanty; B. K. Das (Environmental Monitoring and Assessment, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Status of Hilsa Fishery in Hooghly-Bhagirathi River System and Associated Coastal Waters of Northern Bay of Bengal - A. M. Sajina; V. R. Suresh; K. M. Sandhya; J. Mukherjee; R. K. Manna; B. K. Behera; R. Samanta; T. Maity; S. K. Banik (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Case Study of a Convective Cluster Over the Rain Shadow Region of Western Ghats Using Multi-platform Observations and WRF Model - Soumya Samanta; Kulkarni Gayatri; P. Murugavel; B. Balaji; N. Malap; Y. Jaya Rao; S. M. Deshpande; S. M. Sonbawne; P. Suneetha; Thara V. Prabha (Pure and Applied Geophysics, 2020)

Assessment of adverse impacts of glyphosate-based herbicide, Excel Mera 71 by integrating multi-level biomarker responses in fishes - P. Samanta; S. Pal; A. K. Mukherjee; T. Senapati; J. Jung; A. R. Ghosh (International Journal of Environmental Science and Technology, 2019)

Slope stability assessment and design of remedial measures for Tungnath Temple at Uttarakhand, India: a case study - M. Samanta; P. Punetha; S. Sarkar; A. Dwivedi; M. Sharma (Natural Hazards, 2019)

Disparity in rainfall trend and patterns among different regions: analysis of 158 years’ time series of rainfall dataset across India - Saurav Saha; Debasish Chakraborty; Ranjit Kumar Paul; Sandipan Samanta; S. B. Singh (Theoretical and Applied Climatology, 2018)

Trace metal concentrations in euryhaline fish species from Chilika lagoon: human health risk assessment - S. Parida; S. K. Barik; B. Mohanty; P. R. Muduli; S. K. Mohanty; S. Samanta; A. K. Pattanaik (International Journal of Environmental Science and Technology, 2017)

Dynamics of a food chain model with herd behaviour of the prey - S. P. Bera; A. Maiti; G. P. Samanta (Modeling Earth Systems and Environment, 2016)

Severe Hyperhomocysteinemia Decreases Respiratory Enzyme and Na+-K+ ATPase Activities, and Leads to Mitochondrial Alterations in Rat Amygdala - Janaína Kolling; Emilene B. S. Scherer; Cassiana Siebert; Aline Longoni; Samanta Loureiro; Simone Weis; Letícia Petenuzzo; Angela T. S. Wyse (Neurotoxicity Research, 2016)

Crosstalk Among Disrupted Glutamatergic and Cholinergic Homeostasis and Inflammatory Response in Mechanisms Elicited by Proline in Astrocytes - Samanta Oliveira Loureiro; Daniele Susana Volkart Sidegum; Helena Biasibetti; Mery Stefani Leivas Pereira; Diogo Losch de Oliveira; Regina Pessoa-Pureur; Angela T. S. Wyse (Molecular Neurobiology, 2016)

Hypoxic stress: impact on the modulation of TLR2, TLR4, NOD1 and NOD2 receptor and their down-stream signalling genes expression in catla (Catla catla) - Madhubanti Basu; Mahismita Paichha; Saswati S. Lenka; Rina Chakrabarty; Mrinal Samanta (Molecular Biology Reports, 2016)

Experimental Lung Injury Promotes Changes in Oxidative/Nitrative Status and Inflammatory Markers in Cerebral Cortex of Rats - Maira J. da Cunha; Aline A. da Cunha; Samanta O. Loureiro; Fernanda R. Machado; Felipe Schmitz; Janaína Kolling; Eduardo P. Marques; Angela T. S. Wyse (Molecular Neurobiology, 2015)

Mild Hyperhomocysteinemia Increases Brain Acetylcholinesterase and Proinflammatory Cytokine Levels in Different Tissues - Emilene B. S. Scherer; Samanta O. Loureiro; Fernanda C. Vuaden; Aline A. da Cunha; Felipe Schmitz; Janaína Kolling; Luiz Eduardo B. Savio; Maurício R. Bogo; Carla D. Bonan; Carlos A. Netto; Angela T. S. Wyse (Molecular Neurobiology, 2014)

Experimental lung injury promotes alterations in energy metabolism and respiratory mechanics in the lungs of rats: prevention by exercise - Maira J. da Cunha; Aline A. da Cunha; Emilene B. S. Scherer; Fernanda Rossato Machado; Samanta O. Loureiro; Rodrigo B. Jaenisch; Fátima Guma; Pedro Dal Lago; Angela T. S. Wyse (Molecular and Cellular Biochemistry, 2014)

Identification of MDP (muramyl dipeptide)-binding key domains in NOD2 (nucleotide-binding and oligomerization domain-2) receptor of Labeo rohita - Jitendra Maharana; Banikalyan Swain; Bikash R. Sahoo; Manas R. Dikhit; Madhubanti Basu; Abhijit S. Mahapatra; Pallipuram Jayasankar; Mrinal Samanta (Fish Physiology and Biochemistry, 2013)

Mild hyperhomocysteinemia reduces the activity and immunocontent, but does not alter the gene expression, of catalytic α subunits of cerebral Na+,K+-ATPase - Emilene B. S. Scherer; Samanta O. Loureiro; Fernanda C. Vuaden; Felipe Schmitz; Janaína Kolling; Cassiana Siebert; Luiz Eduardo B. Savio; Bruna M. Schweinberger; Maurício R. Bogo; Carla D. Bonan; Angela T. S. Wyse (Molecular and Cellular Biochemistry, 2013)

Late Paleocene–early Eocene carbon isotope stratigraphy from a near-terrestrial tropical section and antiquity of Indian mammals - A SAMANTA; A SARKAR; M K BERA; JYOTSANA RAI; S S RATHORE (Journal of Earth System Science, 2013)

k nearest neighbor-molecular field analysis on human HCV NS5B polymerase inhibitors: 2,5-disubstituted imidazo[4,5-c]pyridines - S. P. Gupta; S. Samanta; Neeraj Masand; Vaishali M. Patil (Medicinal Chemistry Research, 2013)

Morphological, anatomical and molecular investigation into witches’ broom disease of mamejvo (Enicostemma axillare) - K. Abirami; Anjali Sharma; Jatindra Nath Samanta; V. S. Rana; Kunal Mandal (Phytoparasitica, 2012)

The D ual A rrhenius and M ichaelis– M enten kinetics model for decomposition of soil organic matter at hourly to seasonal time scales - Eric A. Davidson; Sudeep Samanta; Samantha S. Caramori; Kathleen Savage (Global Change Biology, 2012)
Decomposition of soil carbon stocks is one of the largest potential biotic feedbacks to climate change. Models of decomposition of soil organic matter and of soil respiration rely on empirical functions that relate variation in temperature and soil water content to rates of microbial metabolism using soil‐ C substrates. Here, we describe a unifying modeling framework to combine the effects of temperature, soil water content, and soluble substrate supply on decomposition of soluble soil‐ C substrates using simple functions based on process concepts. The model's backbone is the Michaelis–Menten equation, which describes the relationship between reaction velocity and soluble organic‐ C and O 2 substrate concentrations at an enzyme's reactive site, which are determined by diffusivity functions based on soil water content. Temperature sensitivity is simulated by allowing the maximum velocity of the reaction ( V max ) to vary according to A rrhenius function. The D ual A rrhenius and M ichaelis– M enten kinetics ( DAMM ) model core was able to predict effectively observations from of laboratory enzyme assays of β‐glucosidase and phenol‐oxidase across a range of substrate concentrations and incubation temperatures. The model also functioned as well or better than purely empirical models for simulating hourly and seasonal soil respiration data from a trenched plot in a deciduous forest at the H arvard Forest, in northeastern U nited S tates. The DAMM model demonstrates that enzymatic processes can be intrinsically temperature sensitive, but environmental constrains of substrate supply under soil moisture extremes can prevent that response to temperature from being observed. We discuss how DAMM could serve as a core module that is informed by other modules regarding microbial dynamics and supply of soluble‐ C substrates from plant inputs and from desorption of physically stabilized soil‐ C pools. Most importantly, it presents a way forward from purely empirical representation of temperature and moisture responses and integrates temperature‐sensitive enzymatic processes with constraints of substrate supply.

3D QSAR kNN-MFA studies on thiouracil derivatives as hepatitis C virus inhibitors - Vaishali M. Patil; S. P. Gupta; S. Samanta; Neeraj Masand (Medicinal Chemistry Research, 2011)

Image analysis of seafloor photographs for estimation of deep-sea minerals - Rahul Sharma; S. Jai Sankar; Sudeshna Samanta; A. A. Sardar; D. Gracious (Geo-Marine Letters, 2010)

Characterization of Vibrio species isolated from freshwater fishes by ribotyping - P. Mishra; M. Samanta; S. Mohanty; N. K. Maiti (Indian Journal of Microbiology, 2010)

Effects of aggregated classifications of forest composition on estimates of evapotranspiration in a northern Wisconsin forest - D. S. MACKAY; D. E. AHL; B. E. EWERS; S. T. GOWER; S. N. BURROWS; S. SAMANTA; K. J. DAVIS (Global Change Biology, 2002)
Forest management presents challenges to accurate prediction of water and carbon exchange between the land surface and atmosphere, due to its alteration of forest structure and composition. We examined how forest species types in northern Wisconsin affect landscape scale water fluxes predicted from models driven by remotely sensed forest classification. A site‐specific classification was developed for the study site. Using this information and a digital soils database produced for the site we identified four key forest stand types: red pine, northern hardwoods, aspen, and forested wetland. Within these stand types, 64 trees representing 7 species were continuously monitored with sap flux sensors. Scaled stand‐level transpiration from sap flux was combined with a two‐source soil evaporation model and then applied over a 2.5 km × 3.0 km area around the WLEF AmeriFlux tower (Park Falls, Wisconsin) to estimate evapotranspiration. Water flux data at the tower was used as a check against these estimates. Then, experiments were conducted to determine the effects of aggregating vegetation types to International Geosphere– Biosphere Program (IGBP) level on water flux predictions. Taxonomic aggregation resulting in loss of species level information significantly altered landscape water flux predictions. However, daily water fluxes were not significantly affected by spatial aggregation when forested wetland evaporation was included. The results demonstrate the importance of aspen, which has a higher transpiration rate per unit leaf area than other forest species. However, more significant uncertainty results from not including forested wetland with its high rates of evaporation during wet summers.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Photochemical Transformation of the Fungicide Chlorothalonil by Ultra Violet Radiation - S. Samanta; R. K. Kole; L. K. Ganguly; A. Chowdhury (Bulletin of Environmental Contamination and Toxicology, 1997)